RANCANG BANGUN SISTEM INFORMASI EKSEKUTIF BERBASIS WEB DI STMIK YADIKA BANGIL - Teguh Arifianto, Mohammad Sofi (STMIK YADIKA BANGIL, 2018)
Executive information system is an information system that presents the data needed by the staff members of the executive. The system is required in an agency or institution that leaders can access the required information easily and from the leaders can evaluate information and make policies to be applied in the future. STMIK Yadika Bangil not have computerized information systems executives. This institution has only transactional information systems. So in this study was designed and built executive information systems in STMIK Yadika Bangil by leveraging transactional information system database. The transactional database is duplicated and then extracted the data-only data necessary for further transformed into a database and processed by the executive executive information systems. Concept extraction and transformation of data using the Data Warehouse concept. Keywords: Executive information systems, transactional information systems, data warehouseFull Text : pdf